2016
DOI: 10.1016/j.livsci.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of chitosan on nutrient digestibility, blood metabolites and lactation performance in holstein dairy cows

Abstract: Chitosan (CHI), a non-toxic and biodegradable biopolymer has been successfully used in the food, human and veterinary medicine industries, especially because of its antimicrobial properties. This study aimed to investigate the effects of CHI on dry matter intake (DMI), nutrient digestibility, blood metabolites, milk yield and composition, and milk fatty acids profile of lactating dairy cows. Sixteen Holstein cows (91.3715.1 days in milk, 29.8 74.1 kg/d of milk, 610 755 kg of body weight [BW]) were used in a 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 25 publications
8
42
2
Order By: Relevance
“…Until the present study, there has been no study evaluating chitosan and fat source association in dairy cow diets. Mingoti et al (2016), Araujo et al (2015) and Goiri et al (2010b) found no effect of chitosan on dry matter intake (DMI) in dairy cows, beef cattle and sheep, respectively. In the present study, however, chitosan decreased DMI in Table 5 Milk yield and composition of lactating dairy cows fed diets containing chitosan and soybean oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until the present study, there has been no study evaluating chitosan and fat source association in dairy cow diets. Mingoti et al (2016), Araujo et al (2015) and Goiri et al (2010b) found no effect of chitosan on dry matter intake (DMI) in dairy cows, beef cattle and sheep, respectively. In the present study, however, chitosan decreased DMI in Table 5 Milk yield and composition of lactating dairy cows fed diets containing chitosan and soybean oil.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan increased DM and CP digestibility. Araujo et al (2015), Paiva et al (2017), and Mingoti et al (2016) also found DM and CP digestibility increase using dietary chitosan. These studies and the present one used internal markers for daily fecal estimation.…”
Section: Tablementioning
confidence: 93%
“…Treatments were composed of diets with 2 inclusion rates of WRS (0 or 14% diet DM) and 2 doses of CHI (0 or 4 g/kg of DM, Polymar Ciência e Nutrição, Fortaleza, Brazil). Chitosan dose was based on a previous study with beef cattle of our research group (Araújo et al, 2015) and further supported by an experiment with lactating cows (Mingoti et al, 2016). According to the manufacturer, CHI had an apparent density of 0.32 g/mL, pH 7.9, viscosity of 50 cP at 20°C, and deacetylation degree of 86.3%.…”
Section: Animals Experimental Design and Dietsmentioning
confidence: 99%
“…Moreover, chitosan in the rumen environment has been shown to allow for greater permeability of epithelia and reduce in vitro pH, promoting improved digestibility (Benediktsdóttir et al, 2014). Mingoti et al (2016) suggested that the increased digestibility provided by chitosan addition is due to its ability to affect rumen microorganisms and digestive processes, acting mainly on Gram-positive bacteria. This phenomenon explains the improved digestibility of NDF and CP.…”
Section: Discussionmentioning
confidence: 99%
“…The feed was weighed on a digital scale, and its provision was adjusted so that orts accounted for approximately 100 g/kg of the offered DM. Chitosan was placed over the concentrate upon delivery of the total diet in order to visually ensure consumption of the additive in its entirety under animal production conditions, as described by Mingoti et al (2016). During the entire experimental period, samples of ingredients and diets were collected, quartered and packed in identified plastic bags that were stored in a freezer at -20°C for later chemical analysis.…”
Section: Experimental Diets and Handlingmentioning
confidence: 99%